The effectiveness of service quality towards customer complaint: a case of SAJ Ranhill Sdn. Bhd. / Shah Iskandar Mohd Suharto - Mohd Suharto, Shah Iskandar (2018)
In this chapter, the researcher will discuss about the background of study, problem statement, and research objective, research question, scope of study, significant of study, limitation of study, and definition-of terms and the summary about this research. This research is more focusing on customer complaint and complaint management at. SAJ Ranhill Sdn. Bhd. In the background of the study, this research will elaborate about the complaint, service quality, complaint management, customer service and public service. The research question will discuss about the type of medium and type of complaint at SAJ Ranhill Sdn Bhd, in this chapter as well, this research will go through about the information of the importance of this study towards all parties. It will be covered in the significance of study. There are several limitations throughout this research, which are on the period of data gathered, difficulty in obtaining information and also the accuracy of data. Lastly, summary will summarize all the relevant information that included in chapter one.